Cell-free fat extract regulates oxidative stress and alleviates Th2-mediated inflammation in atopic dermatitis - Fu, Zexin; Gu, Qinhao; Wang, Lu; Chen, Lulu; Zhou, Liuyi; Jin, Qiang; Li, Ting; Zhao, Ye; Wu, Sufan; Luo, Xuejiao; Jin, Tingting; Guo, Chengrui (Frontiers in Bioengineering and Biotechnology, 2024)
Atopic dermatitis (AD) is a common inflammatory skin disease that significantly affects patients' quality of life. This study aimed to evaluate the therapeutic potential of cell-free fat extract (FE) in AD. In this study, the therapeutic effect of DNCB-induced AD mouse models was investigated. Dermatitis scores and transepidermal water loss (TEWL) were recorded to evaluate the severity of dermatitis. Histological analysis and cytokines measurement were conducted to assess the therapeutic effect. Additionally, the ability of FE to protect cells from ROS-induced damage and its ROS scavenging capacity both in vitro and in vivo were investigated. Furthermore, we performed Th1/2 cell differentiation with and without FE to elucidate the underlying therapeutic mechanism. FE reduced apoptosis and cell death of HaCat cells exposed to oxidative stress. Moreover, FE exhibited concentration-dependent antioxidant activity and scavenged ROS both in vitro and vivo. Treatment with FE alleviated AD symptoms in mice, as evidenced by improved TEWL, restored epidermis thickness, reduced mast cell infiltration, decreased DNA oxidative damage and lower inflammatory cytokines like IFN-γ, IL-4, and IL-13. FE also inhibited the differentiation of Th2 cells in vitro. Our findings indicate that FE regulates oxidative stress and mitigates Th2-mediated inflammation in atopic dermatitis by inhibiting Th2 cell differentiation, suggesting that FE has the potential as a future treatment option for AD.